IMPLEMENTATION OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) LEARNING MODEL ON TEACHING AND LEARNING READING - Purwo Haryono; Sukasih Ratna Widayanti; Citra Dewi (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
Learning model is very important to use for the success of learning. With an easy model, students will be interested in learning. That is why the researchers did a research in the implementation of the CIRC learning model on learning students’ reading at a vocational high school. This qualitative research data were collected by doing observation, interviews, and documentation. The result showed that the CIRC learning model was successfully applied. This can be seen from the increase in student scores. It was also found that the English teacher experienced difficulties in managing the class when students made presentations. From these obstacles, the solution taken by the teacher was giving assignments to students when their friends make presentations.